Analisis Faktor yang Memengaruhi Minat Penggunaan Learning Management System dengan Model UTAUT - Mirda Azzah Abidah; Tri Lathif Mardi Suryanto; Doddy Ridwandono (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
The use of technology and its development in the world of education helps in improving the quality of education. But the inequality of facilities in the use of inter-school technology in Indonesia remains uneven. Add to this the appearance of covid-19 at that time causes the quality of learning to be reduced because it cannot be performed effectively and efficiently.Learning management system development is a helpful solution to learning problems. SMAN 1 Gedangan building adopted the application of Learning Management System during the covid-19 pandemic. The platform used was the Google Classroom application.But the use of the platform is sustained to this day. With this in mind, researchers would like to explore what factors might influence interest in the use of learning management system. In addition, researchers would like to examine the effects of Learning Management System's continued use. The model in this research is using UTAUT (Unified Theory of Acceptance and Use of Technology). Sampling retrieval using Stratified Random Sampling techniques. The data collection technique involves the distribution of questionnaires through Google form and distribution done in person so that researchers can see for themselves. The respondents in this study numbered 279 students from XI and XII classes. Based on analysis obtained that Perfomance Expectancy, Effort Expectancy, Social Influence significantly affect the Behavior Intention. Apart from these, notices and Facilitating Condition also generate significant results regarding the use of behavior. This means that more and more users are willing to use learning management systems and will be affected by future use of the services and impact on both academic value and the quality of learning.